نكاح المتعة بين أهل السنة والشيعة في تايلاند: Nikāh Mut’ah between Sunnis and Shiites in Thailand - Chuadee, Vinai; Khaled Moawwad., Abdel Tawwab Moustafa; Abdelgayed, Ahmed Fathi Ramadan (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص هذا البحث موضوعه: (نكاح المتعة بين أهل السنة والشيعة في تايلاند) دراسة مقارنة بين فقه السنة وفقه الشيعة بأن يتعرض الباحث بآرائهم الفقهية وأدلتهم ثم يقوم بالمناقشة وبيان الرأي المختار وسبب اختياره لمحاولة الوصول إلى حكم الله في مسألة نكاح المتعة التي اختلف فيها بين أهل السنة والشيعة في تايلاند لاختيار الرأي الأرجح، وبيان كيفية المواجهة للفقه الشيعي في تايلاند، وجاءت المشكلة لما بذل دعاة الشيعة جهودهم وإمكاناتهم في نشر الفقه الشيعي الجعفري كمسألة نكاح المتعة بين أوساط أهل السنة في تايلاند بـإدعاء أنّ هذا مذهب أهل البيت ومصدره من آل محمد صلى الله عليه وسلم، فيتناول الباحث هنا عن أهم نتائج البحث على ما يأتي: إنه من أظهر فرق الشيعة في تايلاند الشيعة الإمامية وهم يدينون بالمذهب الجعفري. وإن حكم نكاح المتعة حرام عند أهل السنة وجائز عند الشيعة. وإن سبب الاختلاف في حكم نكاح المتعة بين الجانبين يرجع إلى اثنين. أولا: اعتماد كل منهما على النصوص القرآنية والسنة الشريفة التي لم يعتمد الآخر عليها. وثانيا: اعتماد كل منهما على نفس النصوص التي اختلف فيها التأويل من الجانبين. وإن أفضل منهج في مواجهة ومناقشة آرائهم في نكاح المتعة التعامل المباشر مع مصادرهم المعتمدة. وإنه لا يجوز التعبّد بالمذهب الجعفري لأنه لا يوجد لديهم كتاب في الفقه ألفه جعفر الصادق نفسه، أو دوّنه له تلامذته وبقي الناس يتداولونه إلى اليوم، كما هو شأن غيره من فقهاء المذاهب الأربعة. Abstract This research is the subject of: (Nikah mut’ah between Sunnis and Shiites in Thailand) a comparative study between Sunni jurisprudence and Shiite jurisprudence by exposing their jurisprudential opinions and evidence, then discussing and clarifying the chosen opinion and the reason for choosing it to try to arrive at God’s judgment on the issue of mut’ah marriage in which the Sunnis and Shiites differed in Thailand to choose the most likely opinion, and to explain how to confront Shiite jurisprudence in Thailand. The problem arose when the Shiite preachers exerted their efforts and capabilities in spreading the Shiite Jaafari jurisprudence as a matter of mut’ah marriage among Sunnis in Thailand, claiming that this is the doctrine of the Ahl al-Bayt and its source is from the family of Muhammad, may God’s prayers and peace be upon him. The researcher here deals with the most important results of the research on the following: It is one of the most prominent Shiite sects in Thailand, the Imamate Shiites, who adhere to the Jaafari school of thought. And the ruling on mut’ah marriage is forbidden by the Sunnis and permissible by the Shiites. And the reason for the difference in the ruling on temporary marriage between the two sides is due to two things. First: Each of them relied on the Qur’anic texts and the honorable Sunnah that the other did not rely on. Secondly, both of them rely on the same texts in which interpretation differs from both sides. The best approach to confronting and discussing their opinions regarding temporary marriage is to deal directly with their approved sources. And it is not permissible to worship the Jaafari school of thought because they do not have a book on jurisprudence that Ja’far al-Sadiq himself wrote, or that his students wrote it down for him, and people continue to circulate it to this day, as is the case with other jurists of the four schools.